If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(4x-2)+12x=2(5x-1)-2(x-6)-5x
We move all terms to the left:
-(4x-2)+12x-(2(5x-1)-2(x-6)-5x)=0
We add all the numbers together, and all the variables
12x-(4x-2)-(2(5x-1)-2(x-6)-5x)=0
We get rid of parentheses
12x-4x-(2(5x-1)-2(x-6)-5x)+2=0
We calculate terms in parentheses: -(2(5x-1)-2(x-6)-5x), so:We add all the numbers together, and all the variables
2(5x-1)-2(x-6)-5x
We add all the numbers together, and all the variables
-5x+2(5x-1)-2(x-6)
We multiply parentheses
-5x+10x-2x-2+12
We add all the numbers together, and all the variables
3x+10
Back to the equation:
-(3x+10)
8x-(3x+10)+2=0
We get rid of parentheses
8x-3x-10+2=0
We add all the numbers together, and all the variables
5x-8=0
We move all terms containing x to the left, all other terms to the right
5x=8
x=8/5
x=1+3/5
| 16=8+4y | | 3z^2+11z+10=0 | | x^2+x=648 | | 3x+2(2x-2)=9 | | -1/3(n+15)=-21 | | 4y2+8y+4=0 | | 6-x/3=1 | | X^2-5x=-x | | 8v=4v2-4 | | 4q2=-8q | | 32=x√3 | | (10/(7+(-5x))=(16/(5+7x)) | | (x+9)x=16^2 | | 8p2+7=0 | | 2+4/9x=2+x | | 5u^2+60u+100=0 | | 2z2=2z | | -19=b-9 | | Y=1.5+x2 | | (x+9)x=256 | | -100+33/(1+r)(r)=0 | | 9q2-5q=-4 | | 7x+35=-35 | | (5-v)(5v+9)=0 | | Y=2+x/0.5 | | x/3+13=21 | | 1/(1+r)*(33/r)-100=0 | | 5^(x-2)=12 | | 6s2+7=0 | | 1/(1+r)(33/r)-100=0 | | (x/5)+11=-9 | | 4s+8=5+4s |